On the Religious and the Secular in Nineteenth-Century Buganda - Zoanni, Tyler (Journal of religion in Africa, 2024)
The case of nineteenth-century Buganda opens up a number of assumptions within scholarship about religion, secularity, and politics in African history. Although much scholarship focuses on European colonizers introduced alien categories such as religion and imposed distinctions between religion and politics, this paper foregrounds a different set of historical transformations in what is now Uganda – transformations that ultimately increased rather than diminished connections between the exercise of political power and markedly religious convictions. Along the way, it locates some of the most important pieces of this story in ‘the precolonial’. This allows the paper to trace the emergence of the category of religion, as well as analyze the sense in which it is meaningful to think of precolonial Buganda as secular at a particular moment. In so doing, the paper puts an African story in dialogue with wider conversations on the secular.